Verses for the dead - Preston, Douglas J.; Child, Lincoln (2018)
"After an overhaul of leadership at the FBI's New York field office, A. X. L. Pendergast is abruptly forced to accept an unthinkable condition of continued employment: the famously rogue agent must now work with a partner. Pendergast and his new teammate, junior agent Coldmoon, are assigned to Miami Beach, where a rash of killings by a bloodthirsty psychopath are distinguished by a confounding M.O.: cutting out the hearts of his victims and leaving them -- along with cryptic handwritten letters -- at local gravestones, unconnected save in one bizarre way: all belonged to women who committed suicide. But the seeming lack of connection between the old suicides and the new murders is soon the least of Pendergast's worries. Because as he digs deeper, he realizes the brutal new crimes may be just the tip of the iceberg: a conspiracy of death that reaches back decades" -- Front jacket flap
Keywords: Pendergast, Aloysius -- (Fictitious character) -- Fiction; United States. -- Federal Bureau of Investigation -- Fiction; Government investigators -- Fiction; Serial murder investigation -- Fiction; Miami Beach (Fla.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Mystery -- Fiction; Fiction; Thrillers (Fiction)